Effects of High-Intensity Position-Specific Drills on Physical and Technical Skill Performance in Elite Youth Soccer Players. Issue 5 (23rd May 2023) - Cuong Le, Cao; Ma'ayah, Fadi; Nosaka, Kazunori; Hiscock, Daniel; Latella, Christopher
Abstract: Cuong Le, C, Ma'ayah, F, Nosaka, K, Hiscock, D, and Latella, C. Effects of high-intensity position-specific drills on physical and technical skill performance in elite youth soccer players. J Strength Cond Res 37(5): e332–e340, 2023—Soccer physical preparation has been extensively researched with previous emphasis on high-intensity interval running and small-sided games. However, neither approach considers positional differences. The purpose of this study was to investigate the feasibility and short-term effects of a novel position-specific conditioning training (PSCT) paradigm on physical and technical abilities of young soccer players. Fifteen male Vietnamese professional youth soccer players (16.1 ± 0.4 years, 171.7 ± 4.8 cm, 63.9 ± 3.8 kg) undertook a 3-week control period followed by a 3-week intervention with PSCT drills performed twice per week. Position-specific conditioning training comprised purposely designed drills for attackers, defenders, and wingers, respectively. The intensity and duration were the same for all drills (4 × 4 minutes at ∼90% heart rate maximum [HRmax], separated by a 4-minute recovery at 70% HRmax) but differed in the technical and tactical actions performed. Outcome measures included Yo-Yo intermittent recovery test level 1, repeated sprint ability, 10-m and 30-m sprint time, and the Loughborough Soccer Passing Test for technical skills in a fatigued and nonfatigued state. Position-specific conditioning training drills induced a desirable intensity for effective conditioning purpose (89.0 ± 2.1% HRmax) with low interplayer variability (coefficient of variation = 2.4%). Yo-Yo intermittent recovery test level 1 performance improved ( p < 0.05) after the control (Δ178.7 ± 203.3 m) and intervention (Δ176.0 ± 225.7 m) periods without a difference between. These results confirmed the feasibility of PSCT as a novel high-intensity training approach for soccer players. Improvements in aerobic capacity were noted, despite no effect on other physical and technical measures. PSCT may be suitable for individual training, return-to-play stages of rehabilitation, during off-season, or in academy settings when time is not a constraint.